Health care finance and the mechanics of insurance and reimbursement - Harrington, Michael K. (Burlington, MA : Jones & Bartlett Learning, 2016)
This book addresses the methods and process for reimbursement, including coding, reimbursement strategies, compliance, financial reporting, case mix index, and external auditing. With up-to-date coverage of the Affordable Care Act, this text will prepare health administration and health information management students with the necessary tools to successfully transition from the classroom to the health care facility. Some of the topics covered include: claims processing; the Affordable Care Act; Medicare Prospective Payment System (Inpatient); Medicare Outpatient Prospective Payment Systems (Non-Inpatient); coding for the non-HIM professional; revenue cycle management; healthcare fraud and abuse; electronic health records and meaningful use; government incentive programs; recovery audit contractors student & instructor resources. -- Edited summary from book
Includes bibliographical references and index.
Keywords: Insurance, Health, Reimbursement; Financial Management; Insurance Claim Reporting